Growth and Yield of Sweet Corn Hybrids Organically Grown During the Dry Season in the Midland with Monsoon Rainfall Pattern - Rike Faradilla; Mohammad Chozin; Sigit Sudjatmiko; Fahrurrozi Fahrurrozi (The University of Lampung, 2025)
The comprehensive evaluation of sweet corn hybrids developed for organic production n needs to be conducted across different environmental conditions prior to their adoption by farmers. This study aimed to assess and compare the growth and yield of 17 sweet corn hybrids grown organically in a midland region characterized by a monsoon rainfall pattern. It was conducted during the dry season from July to October 2024 in Sumber Pakis Village, Pakis District, Malang Regency, East Java Province at an altitude of 550 m above sea level. The experiment was designed in a randomized complete block design with three replications and involved 17 sweet corn hybrids as the treatments. Data were collected for the plant growth performance and the ear yield characteristics. In general, the findings of the study suggest that the dry season that took place throughout the growing period led to drought stress, which negatively impacted the performances of sweet corn plants, including growth and ear yield characteristics of most of the hybrids evaluated. The exception was Caps 22 × Caps 23, which had the ability to maintain normal growth performance. Likewise, only Caps 2 × Caps 5, Caps 5 × Caps 17B, Caps 17B × Caps 23, Caps 22 × Caps 23, and Paragon still produced notable marketable ears.